2017
DOI: 10.3892/ol.2017.7401
|View full text |Cite
|
Sign up to set email alerts
|

PDCD5 regulates cell proliferation, cell cycle progression and apoptosi

Abstract: Abstract. Programmed cell death (PDCD)5 is cloned from human leukemia cell line TF-1. PDCD5 is one of the members of the programmed cell death protein family that is frequently involved in tumor growth and apoptosis. To investigate the molecular and cellular functions of PDCD5, the present study established a PDCD5 stably overexpressing A431 cell line and examined the role of PDCD5 in cell proliferation, cell cycle progression and apoptosis. The data demonstrated that overexpression of PDCD5 significantly inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 80 publications
1
18
0
Order By: Relevance
“…Programmed cell death 5 (PDCD5), known also as TF-1 cell apoptosis-related gene-19 (TFAR19), was originally recognized in human leukemia TF-1 cells having serum withdrawal-induced apoptosis (Ha et al, 2021;Li et al, 2018). PDCD5 was declared downregulated in a lot of the human malignancies, including breast cancer (Hedenfalk et al, 2001) lung adenocarcinoma and hepatocellular carcinoma (Ma et al, 2019), as well as ovarian cancer (Gao et al, 2015).…”
Section: Research Articlementioning
confidence: 99%
“…Programmed cell death 5 (PDCD5), known also as TF-1 cell apoptosis-related gene-19 (TFAR19), was originally recognized in human leukemia TF-1 cells having serum withdrawal-induced apoptosis (Ha et al, 2021;Li et al, 2018). PDCD5 was declared downregulated in a lot of the human malignancies, including breast cancer (Hedenfalk et al, 2001) lung adenocarcinoma and hepatocellular carcinoma (Ma et al, 2019), as well as ovarian cancer (Gao et al, 2015).…”
Section: Research Articlementioning
confidence: 99%
“…At present, twelve members of PDCD protein family are identified, including PDCD1-PDCD12. 16 It has reported that PDCD5 is lowly expressed in various tumors, such as lung cancer, 29 gastric cancer 30 and liver cancer. 31 In this study, we also confirmed that PDCD5 expression was downregulated in CSCC tissue and cells.…”
Section: Discussionmentioning
confidence: 99%
“…Programmed cell death 5 (PDCD5), one of the programmed cell death proteins, is abnormally expressed in many cancers and plays an important role in cell proliferation, apoptosis and metastasis. [14][15][16] Fan et al 17 have indicated that PDCD5 can inhibit cell growth and invasion, and promote cell apoptosis in hepatic cancer. However, whether the regulatory effect of miR-766 on CSCC is related to PDCD5 is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that H-PDCD5 promotes its cleavage and activation, leading to the occurrence of apoptosis (59, 60). H-PDCD5 causes cell apoptosis by regulating the expression of BCL-2 family members (61). For the TP53 gene, the presence of PDCD5 and drug treatment increases the activity of TP53, thereby increasing the interaction between PDCD5 and TP53 to induce cell apoptosis (62).…”
Section: Discussionmentioning
confidence: 99%